Keterlibatan Perempuan, Selisih Kompensasi, dan Kinerja Keuangan - Adji, Elizabeth Karina; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2022)
The purpose of the study was to see the effect of women's involvement in the board of directors on the company's financial performance. The researcher also added the variable of director compensation difference as a moderator variable on the effect of women's involvement in the board of directors on the company's financial performance. The sample used in this study was taken by purposive sampling method and obtained 211 observation samples. This study uses Partial Least Square (PLS) Regression Model analysis to answer the two hypotheses proposed. The results showed that the involvement of women in the board of directors can positively affect the company's financial performance and the difference in compensation in the board of directors can weaken the effect. The results of the research are expected to be a reference for the authorities specifically in considering the involvement of women in the board of directors and determining the compensation gap, because it can affect financial performance. Keywords: Women Involvement; Top Management; Board Of Directors Compensation Gap; Company's Financial Performance.